Nouveaux enjeux de sécurité spatiale - Florence Gaillard-Sborowsky (L'Espace Politique)
Ensuring the security of outer space has become a crucial issue for a transforming space ecosystem, characterized by the proliferation of actors, the development of commercial interests, and the growing dependence of societies and States on space systems. A space diplomacy has emerged, built upon the development of international space law. However, caught between the defense of national interests and the necessary multilateral approach, diplomatic processes are slowed down by oppositions between major space powers, oscillating between competition, rivalry, and antagonism. Alternative normative frameworks are gaining prominence, challenging the traditional regulatory paradigm. The current imperative is the construction of a comprehensive space security framework that facilitates the safe and sustainable utilization of this unique environment, amidst a context of multifaceted tensions.